Human solCD39 inhibits injury-induced development of neointimal hyperplasia - Drosopoulos, Joan H. F.; Kraemer, Rosemary; Shen, Hao; Upmacis, Rita K.; Marcus, Aaron J.; Musi, Elgilda (Thrombosis and Haemostasis, 2010)
Blood platelets provide the initial response to vascular endothelial injury, becoming activated as they adhere to the injured site. Activated platelets recruit leukocytes, and initiate proliferation and migration of vascular smooth muscle cells (SMC) within the injured vessel wall, leading to development of neointimal hyperplasia. Endothelial CD39/NTPDase1 and recombinant solCD39 rapidly metabolise nucleotides, including stimulatory ADP released from activated platelets, thereby suppressing additional platelet reactivity. Using a murine model of vascular endothelial injury, we investigated whether circulating human solCD39 could reduce platelet activation and accumulation, thus abating leukocyte infiltration and neointimal formation following vascular damage. Intraperitoneally-administered solCD39 ADP -ase activity in plasma peaked 1 hour (h) post-injection, with an elimination half-life of 43 h. Accordingly, mice were administered solCD39 or saline 1 h prior to vessel injury, then either sacrificed 24 h post-injury or treated with solCD39 or saline (three times weekly) for an additional 18 days. Twenty-four hours post-injury, solCD39-treated mice displayed a reduction in platelet activation and recruitment, P-selectin expression, and leukocyte accumulation in the arterial lumen. Furthermore, repeated administration of solCD39 modulated the late stage of vascular injury by suppressing leukocyte deposition, macrophage infiltration and smooth muscle cell (SMC) proliferation/migration, resulting in abrogation of neointimal thickening. In contrast, injured femoral arteries of saline-injected mice exhibited massive platelet thrombus formation, marked P-selectin expression, and leukocyte infiltration. Pronounced neointimal growth with macrophage and SMC accretion was also observed (intimal-to-medial area ratio 1.56 ± 0.34 at 19 days). Thus, systemic administration of solCD39 profoundly affects injury-induced cellular responses, minimising platelet deposition and leukocyte recruitment, and suppressing neointimal hyperplasia.
Keywords: CD39; endothelial E-NTPDase1; arterial injury; platelet activation; vascular stenosis